Ciri Tanda Kusta terhadap BTA Swab Hidung Siswa SD Di Daerah Endemis Kusta Kabupaten Kayong Utara - Kuswiyanto Kuswiyanto (Poltekkes Kemenkes Pontianak, 2015)
Abstract: Related Characteristics Of Leprosy Sign To BTA Of Nose Swab In Elementary School Children In Endemic Areas Of Leprosy In Kayong Utara. The aims of this research were to determine the relationship of the sign of leprosy to the microscopic characteristics of BTA of nose swab in elementary school children living in the environment around the leper (endemic areas). This research was descriptive analytic research by inspecting the sign characteristic diagnose leprosy and nose swab microscopic elementary school children around the leper (endemic areas) as many as 61 children. The sample distribution was 35 men (57.4%) and 26 women (42.6%). The distribution by age, 10 years was 26 people (42,6%), 11 years was 22 people (36,1%) and 12 years was 13 (21,3%). The results showed that characteristic sign of leprosy was 1 person (1,68%), the results of Acid Resistant Bacteria (AFB) was 1 person (1.68%). Based on the results of this research there is a characteristic sign of the leprosynose swab in elementary school children in endemic areas of leprosy in the district of North Kayong, where p= 0.016 (p <0.05).Abstrak : Ciri Tanda Kusta Terhadap BTA Swab Hidung Siswa SD Di Daerah Endemis Kusta Kabupaten Kayong Utara. Penelitian ini bertujuan untuk mengetahui hubungan ciri tanda kusta terhadap mikroskopis BTA swab hidung penyebab kusta pada siswa SD yang tinggal di lingkungan sekitar penderita kusta (daerah endemis). Penelitian ini bersifat deskriptif analitik. pemeriksaan dimulai dengan melakukan anamnesa ciri tanda kusta dan mikroskopis BTA swab hidung siswa SD di sekitar penderita kusta (daerah endemis) sebanyak 61 siswa. Distribusi sampel laki-laki sebanyak 35 orang (57,4%) dan perempuan 26 orang (42,6%). Berdasarkan umur 10 tahun sebanyak 26 orang (42,6%),11 tahun sebanyak 22 orang (36,1%) dan 12 tahun sebanyak 13 orang (21,3%). Hasil penelitian menunjukkan ciri tanda kusta sebanyak 1 orang (1,68%), hasil pemeriksaan Bakteri Tahan Asam (BTA) diperoleh sebanyak 1 orang (1,68%). Berdasarkan hasil penelitian terdapat hubungan ciri tanda kusta terhadap BTA Swab Hidung pada siswa Sekolah Dasar di daerah endemis kusta di kabupaten Kayong Utara, dengan p = 0,016 (p< 0,05).